Growth of ErAs nanodots by molecular beam epitaxy for application to tunneling junctions in multijunction solar cells. (6th January 2016) - Hung, Chao-Yu; Sogabe, Tomah; Miyashita, Naoya; Okada, Yoshitaka
Abstract: ErAs nanodots (NDs) grown on GaAs(001) substrates by using molecular beam epitaxy (MBE) were investigated. Atomic force microscope images indicate that the size of ErAs NDs increases with deposition time and growth temperature. A calibration was performed to determine the deposition rate of ErAs in order that the size of NDs can be accurately controlled and hence optimized. Local current flow images and surface profiles around ErAs NDs were simultaneously measured to clarify the local conductivity distribution corresponding to a real space profile. Furthermore, we also fabricated and characterized an ErAs-ND-embedded GaAs tunnel junction (TJ), which resulted in a voltage drop of 30 mV for 15 A/cm 2 operation current equivalent to 1000 suns concentration, which is less than one-third of that of a conventional heavily doped tunnel junction.